Hydranencephaly the most severe presentation of fetal cerebral stroke: a propos of two cases - Lacunza Paredes, Rommel Omar (2014)
Hydranencephaly is rare brain malformation characterized by complete or partial absence of the cerebral hemispheres, caused by occlusion of the carotid arteries in early stages of pregnancy, associated with multiple possible causal factors. We present two cases with postnatal confirmation and review of the literature.